Acute Ventricular Wall Thickening: Sepsis, Thrombotic Microangiopathy, or Myocarditis? - Nicolas De Schryver; Delphine Hoton; Diego Castanares-Zapatero; Philippe Hantson (Case Reports in Cardiology)
Background. Acute myocardial oedema has been documented in experimental models of ischemia-reperfusion injury or sepsis and is usually investigated by magnetic resonance imaging. Purpose. We describe a case of acute ventricular wall thickening documented by echocardiography in a patient developing sepsis and thrombotic microangiopathy. Case Description. A 40-year-old woman, with a history of mixed connective tissue disease, was admitted with laryngeal oedema and fever. She developed Streptococcus pneumoniae septicaemia and subsequent laboratory abnormalities were consistent with a thrombotic microangiopathy. Echocardiography revealed an impressive diffuse thickening of the whole myocardium (interventricular septum 18 mm; posterior wall 16 mm) with diffuse hypokinesia and markedly reduced left ventricular ejection fraction (31%). There was also a moderate pericardial effusion. Echocardiography was normal two months before. The patient died from acute heart failure. Macroscopic and microscopic examination of the heart suggested that the ventricular wall thickening was induced by oedematous changes, together with an excess of inflammatory cells. Conclusion. Acute ventricular wall thickening that corresponded to myocardial oedema as a first hypothesis was observed at echocardiography during the course of septicaemia complicated by thrombotic microangiopathy.